Teachers’ Perceptions and Management of Trauma-Related Behaviours among Pupils Living with Non-Biological Caregivers in Ilorin South, Kwara State, Nigeria - Idowu Oluwabamise Odebode; Eniola Keji Ola-Alani; Oluwakemi Dorcas Lawal (Universitas Islam Bunga Bangsa Cirebon, 2026)
This study is situated within the growing prevalence of children living with non-biological caregivers, commonly referred to as pseudo-parents, particularly in many African societies where extended family caregiving arrangements are widespread. Teachers play a critical role in identifying and managing trauma-related behaviours; however, limited empirical research exists on teachers’ perceptions and responses to such pupils in Nigerian primary schools. Specifically, the study investigated the prevalence of such pupils in classrooms, teachers’ recognition of trauma indicators, and differences in trauma management practices based on teaching experience. A quantitative research design was adopted. The population consisted of 1,166 qualified primary school teachers, of whom 300 were selected using stratified random sampling. Data were collected using the Teachers’ Experience of Adopted Pupils Questionnaire (TEAPQ), and 295 valid responses were analysed using descriptive statistics, t-tests, and ANOVA at a 0.05 significance level. Findings revealed that all participating teachers reported having at least one pupil raised by non-biological caregivers. Teachers moderately recognised trauma-related behaviours such as low self-esteem, absenteeism, and moodiness, but overall trauma identification remained limited. While teaching experience did not significantly influence recognition of trauma, it significantly affected trauma management strategies, with more experienced teachers demonstrating stronger management practices. The study concludes that trauma-related needs of pupils raised by pseudo-parents are insufficiently addressed in classrooms due to gaps in teacher preparedness. The research highlights the need for structured trauma-informed teacher training, strengthened school support systems, and policy interventions aimed at improving educational outcomes for vulnerable pupils.